2020
DOI: 10.3390/ijerph17051727
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte-To-Monocyte Ratio as the Best Simple Predictor of Bacterial Infection in Patients with Liver Cirrhosis

Abstract: Background and aim: The aim of this study was to assess the diagnostic performance of new morphology-related indices and Child–Turcotte–Pugh (CTP) and Model for End-Stage Liver Disease (MELD) scores during hospitalization in predicting the onset of bacterial infection in patients with liver cirrhosis. Material and methods: A total of 171 patients (56.9% males; median age 59 years; total number of hospitalizations 209) with liver cirrhosis were included in this observational study. The diagnosis of cirrhosis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 41 publications
(44 reference statements)
4
36
1
1
Order By: Relevance
“…NLR is a non-invasive marker that can be used to predict the occurrence of in-hospital infections in patients with decompensated liver cirrhosis (17). In a study conducted by Piotrowski et al, an association between NLR and the presence of infection in patients with liver cirrhosis was identified but with low diagnostic accuracy (AUC=0.606) (18).…”
Section: Discussionmentioning
confidence: 99%
“…NLR is a non-invasive marker that can be used to predict the occurrence of in-hospital infections in patients with decompensated liver cirrhosis (17). In a study conducted by Piotrowski et al, an association between NLR and the presence of infection in patients with liver cirrhosis was identified but with low diagnostic accuracy (AUC=0.606) (18).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating studies have demonstrated that LMR was a readily available and independent prognostic biomarker in predicting the poor prognosis of patients with various clinical conditions, including liver cirrhosis, cerebral venous sinus thrombosis, colorectal cancer and peripheral arterial occlusive disease. 14–17 Moreover, numerous investigators have detected the predictive effect of LMR in predicting the clinical outcomes in some inflammatory diseases. Cherfane et al explored the predictive value of LMR in ulcerative colitis (UC) and found that low LMR might be effective, readily available, and low-cost biomarkers to identify disease activity in UC patients.…”
Section: Discussionmentioning
confidence: 99%
“…LMR has long been introduced as an inflammatory marker in various clinical conditions, including liver cirrhosis, cerebral venous sinus thrombosis, colorectal cancer and peripheral arterial occlusive disease. 14–17 Moreover, LMR were also reported to be associated with adverse outcome in various cardiovascular diseases including myocardial infarction, heart failure and aortic dissection. 18–20 As mentioned above, a systemic inflammatory status contributes to poor prognosis in CS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the LM ratio is being studied as a potential prognosis predictor in cancer patients [11,[37][38][39]. Besides being a novel marker of the baseline inflammatory response, the LM ratio decreases in several clinical conditions, including bacterial infections, osteoporosis, stroke, acute rheumatic fever, and coronary artery atherosclerosis [14,16,[40][41][42][43]. Because an unexpected decrease in the LM ratio may be associated with poor outcomes in various clinical circumstances, its clinical application as a prognostic factor is being closely investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The LM ratio can predict the prognosis of patients with colorectal, ovarian, and esophageal cancers [11][12][13]. In addition, it may also be associated with infection in patients with liver cirrhosis, prediction of osteoporosis, and mortality of patients with coronavirus disease 2019 [14][15][16][17]. Furthermore, in patients with head and neck cancer, low lymphocyte count is related to increased tissue adhesion or tissue damage [18].…”
Section: Introductionmentioning
confidence: 99%